„…z polska — po rosyjsku”, czyli o tym, jak Polacy używają ruszczyzny - Michał Sarnowski (Studia Rossica Posnaniensia)
This article is an attempt to reflect on Poles' attitude towards the Russian language. Its aim is to reconstruct various “Polish views of Russian” in their objective dimension (with no intention to evaluate or criticise). Three stereotypical pictures of the Russian language present in the Polish common consciousness recreated by the author are based on range of language material. The description of “the three pictures of Russian in the Polish head” (“Polish common knowledge about Russian”) indicates the instrumentality of this language, which occurs in three hypostases. For the first image it is the usual instrumentality of communication (rossicum is an addition and an excess of information within a Polish text), for the second image the instrumentality acquires unambiguously pragmatic features and the rossicum becomes an instrument of effective action, and for the third picture the instrumentality of Russian elements sets in motion the symbolic-cognitive (creating a sense) function of Russian in Polish text.